Relationships Between Na+ Distribution, Concerted Migration, and Diffusion Properties in Rhombohedral NASICON. Issue 30 (24th June 2020) - Zou, Zheyi; Ma, Nan; Wang, Aiping; Ran, Yunbing; Song, Tao; Jiao, Yao; Liu, Jinping; Zhou, Hang; Shi, Wei; He, Bing; Wang, Da; Li, Yajie; et al.
Abstract: Rhombohedral NaZr2 (PO4 )3 is the prototype of all the NASICON‐type materials. The ionic diffusion in these rhombohedral NASICON materials is highly influenced by the ionic migration channels and the bottlenecks in the channels which have been extensively studied. However, no consensus is reached as to which one is the preferential ionic migration channel. Moreover, the relationships between the Na + distribution over the multiple available sites, concerted migration, and diffusion properties remain elusive. Using ab initio molecular dynamics simulations, here it is shown that the Na + ions tend to migrate through the Na1–Na3–Na2–Na3–Na1 channels rather than through the Na2–Na3–Na3–Na2 channels. There are two types of concerted migration mechanisms: two Na + ions located at the adjacent Na1 and Na2 sites can migrate either in the same direction or at an angle. Both mechanisms exhibit relatively low migration barriers owing to the potential energy conversion during the Na + ions migration process. Redistribution of Na + ions from the most stable Na1 sites to Na2 on increasing Na + total content further facilitates the concerted migration and promotes the Na + ion mobility. The work establishes a connection between the Na + concentration in rhombohedral NASICON materials and their diffusion properties. Abstract : Two concerted ion migration mechanisms, both lowering the energy barrier, are found in rhombohedral NASICON. The decrease is caused by energy transfer between ions at the high energy Na2 site and the low energy Na1 site, analogously to Newton's cradle. Increasing Na + content increases the number of Na + configurations of "Na2 + Na1 + Va(Na2)", which facilitates concerted migration and promotes Na + mobility.